Implementation of marketing campaign through Social Media in the context of Bangladesh: A case study - Ahmed, Wasifa (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2014.